PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BEI TAHUN 2012-2014 - Amalia Nur Chasan; Sabtarini Kusumaningsih (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
The company's goals can be achieved through the implementation of financialmanagement functions with caution and appropriate considering any financial decisionstaken will affect other financial decisions that will affect the value of the company. Thefunding decision will determine the company's ability to carry out its operating activities andthe effect on the risk for the company itself. Financing using debt is too high will increase thecompany's financial risk and ultimately into the financial crisis (financial distress).This study researcher influence profitability, dividend policy and the size of the debtstructure of the company to a manufacturing company in 2012-2014. By using multiple linearregression analysis technique. Samples obtained are 16 companies. Results of the analysisshowed that profitability and dividend policy have significant negative effect on the debtpolicy, while the size of the company does not have a significant effect. The most influentialvariable is profitability. Determination coefficient is 0.344, which means the debt policyvariables explained 34.4% by the variable profitability, dividend policy and the size of thecompany while the rest influenced by other variables.Keywords: debt policy, profitability, dividend policy, the size of the company